Open-label, cluster randomised controlled trial and economic evaluation of a brief letter from a GP on unscheduled medical contacts associated with the start of the school year: the PLEASANT trial. Issue 4 (20th April 2018) - Julious, Steven A; Horspool, Michelle J; Davis, Sarah; Franklin, Matthew; Smithson, W Henry; Norman, Paul; Simpson, Rebecca M; Elphick, Heather; Bortolami, Oscar; Cooper, Cindy
Abstract : Background: Asthma is seasonal with peaks in exacerbation rates in school-age children associated with the return to school following the summer vacation. A drop in prescription collection in August is associated with an increase in the number of unscheduled contacts after the school return. Objective: To assess whether a public health intervention delivered in general practice reduced unscheduled medical contacts in children with asthma. Design: Cluster randomised trial with trial-based economic evaluation. Randomisation was at general practice level, stratified by size of practice. The intervention group received a letter from their general practitioner (GP) in late July outlining the importance of (re)taking asthma medication before the return to school. The control group was usual care. Setting: General practices in England and Wales. Participants: 12 179 school-age children in 142 general practices (70 randomised to intervention). Main outcome: Proportion of children aged 5–16 years who had an unscheduled contact in September. Secondary endpoints included collection of prescriptions in August and medical contacts over 12 months (September–August). Economic endpoints were quality-adjusted life-years gained and health service costs. Results: There was no evidence of effect (OR 1.09; 95% CI 0.96 to 1.25 against treatment) on unscheduled contacts in September. The intervention increased the proportion of children collecting a prescription in August by 4% (OR 1.43; 95% CI 1.24 to 1.64). The intervention also reduced the total number of medical contacts between September–August by 5% (incidence ratio 0.95; 95% CI 0.91 to 0.99). The mean reduction in medical contacts informed the health economics analyses. The intervention was estimated to save £36.07 per patient, with a high probability (96.3%) of being cost-saving. Conclusions: The intervention succeeded in increasing children collecting prescriptions. It did not reduce unscheduled care in September (the primary outcome), but in the year following the intervention, it reduced the total number of medical contacts. Trial registration number: ISRCTN03000938 ; Results.